2003
DOI: 10.1210/en.2002-0137
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of Steroidogenic Factor-1 and FTF/LRH-1 in the Rodent Ovary

Abstract: Steroidogenic factor-1 (SF-1) (NR5A1) is an orphan nuclear receptor that plays a premier role in ovarian organogenesis. Recent studies document mRNA expression of the structurally related factor NR5A2 (FTF, LRH-1, SF-2) in the adult ovary and more specifically in granulosa cells and luteal cells but not theca cells. Conversely, SF-1 was shown to be expressed at higher levels in theca/interstitial cells. These latter observations raised the possibility that FTF/LRH-1 may control target gene expression in granul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
131
0
4

Year Published

2004
2004
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(140 citation statements)
references
References 36 publications
4
131
0
4
Order By: Relevance
“…Moreover, overexpression of constitutively active mutant FOXO1, which prevents aromatase stimulation by FSH and activin, also decreases SF-1 expression [58]. Levels of SF-1 protein do not exhibit major changes during follicular growth or in response to low levels of FSH in culture but decrease rapidly after the LH surge along with the downregulation of aromatase [115], further supporting the idea of an important role for SF-1 in the regulation of aromatase expression.…”
Section: Cis-elements In the Ovarian Promoter And Their Regulationmentioning
confidence: 67%
See 1 more Smart Citation
“…Moreover, overexpression of constitutively active mutant FOXO1, which prevents aromatase stimulation by FSH and activin, also decreases SF-1 expression [58]. Levels of SF-1 protein do not exhibit major changes during follicular growth or in response to low levels of FSH in culture but decrease rapidly after the LH surge along with the downregulation of aromatase [115], further supporting the idea of an important role for SF-1 in the regulation of aromatase expression.…”
Section: Cis-elements In the Ovarian Promoter And Their Regulationmentioning
confidence: 67%
“…In fact, in vitro translated mouse SF-1 and LRH-1 proteins [104] or SF-1 expressed in bacteria [55] bind to oligonucleotides containing the NREa present in the aromatase gene. However, because both factors are expressed in granulosa cells [115,116], whether SF-1 or LRH-1 or both are important for aromatase expression in these cells remains under debate (describe below), although evidence suggests that SF-1 has a more prominent role.…”
Section: Cis-elements In the Ovarian Promoter And Their Regulationmentioning
confidence: 99%
“…Harvesting of the indicated tissues was done at the middle of the dark period. FTF ϩ/Ϫ mice were a generous gift from Dr. L. Belá nger (Laval University, Quebec) and have been described previously (23). FTF ϩ/Ϫ mice were received at the Virginia Commonwealth Animal Facility after at least 10 generations of inbreeding.…”
Section: Methodsmentioning
confidence: 99%
“…This nuclear receptor plays important developmental functions in the mouse, as demonstrated by the genetic dissection of LRH-1 KO mice (Falender et al, 2003;Pare et al, 2004). LRH-1À/À mice die at e6.5-7.5, due to profound developmental defects, such as impaired node formation and gastrulation (Pare et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…During adulthood, LRH-1 plays important roles in cholesterol and lipid homeostasis by controlling the expression of genes involved in these metabolic pathways (for a review see Fayard et al, 2004). Several studies reported elevated expression of LRH-1 in granulosa cells and corpus luteum of the ovary, suggesting potential functions for this nuclear receptor in follicular growth and function (Falender et al, 2003;Hinshelwood et al, 2003). By controlling expression of cyclin E1 and D1 through interaction with b-catenin, LRH-1 has recently been shown to promote intestinal cell renewal (Botrugno et al, 2004).…”
Section: Introductionmentioning
confidence: 99%